PENGARUH PENERAPAN PERMAINAN TRADISIONAL KUCING DAN TIKUS TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 3 PEKANBARU - Marliza Marliza; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The objectives of this research are (1) to know the student’s gross motor skills among the age of 4-5 years old before implementing the cat and mouse game at the state kindergarten of Pembina 3 Pekanbaru, (2) to know the students’ gross motor skills among the age of 4-5 years old after implementing the state kindergarten of Pembina 3 Pekanbaru, (3) to know whether or not there is significant effect of the cat and mouse game toward the students’ gross motor skills among the age of 4-5 years old at the state kindergarten of Pembina 3 Pekanbaru. This research is an experimental research conducted to know the effect of a variable in controlled condition. The subject of the research was the students at the state kindergarten of Pembina 3 Pekanbaru from the age of 4-5 years old in class A. There are 18 students in class A including 8 boys and 10 girls. In collecting data of the research, the writer used observation and documentation. From the research finding, it was concluded that : (1) the students’ gross motor skills among the age of 4-5 years old at the state kindergarten of Pembina 3 Pekanbaru before implementing the activity of the cat and mouse traditional game were classified as develop, (2) the students’ gross motor skills among the age of 4-5 years old at the state kindergarten of Pembina 3 Pekanbaru after implementing the activity of the cat and mouse traditional game were classified as develop based on the writer’s expectation, (3) implementing the cat and mouse traditional game has significant effect toward the students’ gross motor skills among the age of 4-5 years old at the state kindergarten Pembina 3 Pekanbaru. This can be known that there is significant difference of enhancement from the students’ gross motor skills before and after treatment. The implementation of the cat and mouse traditional game has significant effect at 56.25% toward the students’ gross motor skills among the age of 4-5 years old at the state kindergarten of Pembina 3 Pekanbaru.Keywords : The cat and mouse traditional game, gross motor skills.